Analysis of the Effectiveness of Campaign Props in Increasing Voter Participation in Medan City in the 2024 Election - Lubis, Ahmad Muthma Indra; Ginting, Bengkel; Achmad, Nurman (Universitas Medan Area, 2025)
This study analyzes the effectiveness of Campaign Props (APK) in increasing public participation in the 2024 Election in Medan City, using descriptive and causal quantitative methods, such as surveys, interviews, and secondary data analysis. The results show that APK positively and significantly affects community participation, especially in young groups, men, and highly educated voters. Positive perceptions of APKs increased participation by 59.1%, although the effectiveness of APKs also depends on the design elements and transparency of the message. The research emphasizes the importance of inclusive, educational, and relevant political communication strategies to build a positive attitude toward the Election. It was found that the community's Attitude affects participation more than the number and quality of APKs alone. Therefore, it is necessary to manage APKs with a persuasive approach to strengthen public trust and the legitimacy of the democratic process.